Barriers to e-commerce technologies adoption in third party logistics companies - Yaakub, Sabariah (2010)
This paper focuses on the barriers to e-commerce technologies adoption in third party logistics companies in Malaysia.Despite multiple benefits, such as improved accuracy of information dissemination, improved product movement visibility and better customer service levels, the level of ecommerce technologies adoption among the third party logistics companies in Malaysia are not high because of several barriers such as data communication too slow and the customers not ready for ecommerce.